Integrasi Pendekatan STEM (Science, Technology, Enggeenering and Mathematic) Untuk Peningkatan Keterampilan Berpikir Kritis Siswa Sekolah Dasar - Elisabeth Irma Novianti Davidi; Eliterius Sennen; Kanisius Supardi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
Improving the quality of education in Indonesia can be developed through the implementation of education reform. One form of educational reform can be done by using a learning approach that can assist teachers in producing experts using the STEM (Science, Technology, Engineering, and Mathematics) approach. The initial findings revealed only about 47.8% of elementary school students in Wae Ri'i sub-district (grade V) who still had not achieved satisfactory scientific and mathematical scores according to the minimum passing grade. This study aims to see the effectiveness of the STEM approach in improving the critical thinking skills of elementary school students in Wae Ri'i District. The research method used is an experimental design with Non Equivalent Control Group Design. The research subjects were elementary school students in five (5) elementary schools in Wae Ri'i District. The results shows the sig (2-tailed) value of Equal variances is assumed to be 0.000 <0, 05. Therefore, Ho is rejected and Ha is accepted, which means that there is a significant difference in critical thinking skills after students used the STEM-PBL approach, compared to innovative K13 approach. The average scores of the control class critical thinking skills for the pre-test and post-test were 38 and 79.5. The fixed coefficient is 0.676 and is significant at 0.000. This means that the correlation is positive. Therefore, learning with STEM approach is proven to be effective in improving the critical thinking skills of elementary school students in Wae Ri'i sub-district.